2000
DOI: 10.2460/javma.2000.217.1870
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with racing performance of Thoroughbreds undergoing lag screw repair of condylar fractures of the third metacarpal or metatarsal bone

Abstract: Results suggest that female horses with displaced condylar fractures and male horses with nondisplaced condylar fractures are more likely to be referred for treatment. The effect of sex on outcome for these horses cannot be clearly separated from the effect of fracture configuration. When adjusted for fracture configuration, males were 6 times as likely as females to race after surgery. When adjusted for sex, horses with nondisplaced fractures were 17 times as likely as horses with displaced fractures to race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 13 publications
7
56
0
Order By: Relevance
“…Earnings may also be heavily influenced by tactics [5,6]. Furthermore, earnings normally decline with age as younger animals have age-restricted race entry opportunities and supplemented purses [15,23,24], and sex has a strong influence, with entire males having increased potential earnings levels due to their worth to the TB breeding industry [13,14]. Consideration of the advantages of the commonly used outcome measures identified that no measure was ideal, with the highest scoring measures only achieving around half of the 15 specified criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Earnings may also be heavily influenced by tactics [5,6]. Furthermore, earnings normally decline with age as younger animals have age-restricted race entry opportunities and supplemented purses [15,23,24], and sex has a strong influence, with entire males having increased potential earnings levels due to their worth to the TB breeding industry [13,14]. Consideration of the advantages of the commonly used outcome measures identified that no measure was ideal, with the highest scoring measures only achieving around half of the 15 specified criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cast was removed within 24 h after recovery in 21 cases (81%). Horses were hospitalised for an average of 6 days after fracture fixation. The mean time between fracture repair and screw removal was 14 weeks [10–36].…”
Section: Resultsmentioning
confidence: 99%
“…Horses with non-displaced fractures were 17 times more likely to resume racing than horses with displaced fractures after treatment with lag-screw fixation (Martin 2000). Similar fracture configurations may carry a better prognosis if found in the Mt3 rather than Mc3 (Bassage and Richardson 1998).…”
Section: 8 3 Treatment and Outcomementioning
confidence: 99%